The real estate market in China. - Hon, Lawrence Chin Kong. (2009)
The China real property market is rather imperfect in that at some point in the property cycle, sentiment almost always outweighs the fundamentals. This is true of the current market. The returns from real property investment is largely affected by the price movements which is dependent on how well developers can influence the investors' sentiment. In many ways, this depends on media's coverage of the market. But still, economists and others assume that the China real property market, like many market, is near perfect and therefore lend themselves to some scientific analysis.